Penerapan Data Mining Dalam Analisis Penilaian Kinerja Pegawai Menerapkan Metode K-Means - Supriadi Sahibu; Rismawati Bambang; Imran Taufik; Agusriandi Agusriandi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
The organization, including local government agencies, in the face of increasingly fierce competition, must improving employee performance if they want to exist. As an effort to improve employee performance, various strategies were needed, one of which is clustering analysis of employee performance. Clustering analysis is very important in an effort to gain knowledge from employee activities quickly compared to manual methods. Therefore, in this study an analysis of employee performance was carried out based on the Employee Performance Targets (SKP), which was divided into 2, namely the 2020 SKP Printout and the 2021 SKP questionnaire. From the results of the K-Means Cluster it produced a more convincing questionnaire SKP cluster because there was a distribution that was more dominated by employee performance that good and the outliers are of little value, and the difference in the Sum of Square values of the SKP printout and questionnaire clusters that not too far away, only 21% so that the characteristics of the cluster results are almost identical. Cluster results described the real conditions of employee performance.